Dampak dan Penerapan Komunikasi Intrapersonal melalui Media Sosial - Azizah savira; Wiratri Anindhita; Maulina Larasati Putri (Prodi Ilmu Komunikasi Fakultas Ilmu Sosial dan Ilmu Politik USB YPKP, 2024)
Intrapersonal communication, which refers to an individual's internal process of understanding oneself, values, and identity, has undergone a significant transformation on social media. Digital identity is becoming increasingly important in shaping self-perception and social interactions, but it also creates pressure to maintain a perfect image. Social media facilitates deep self-reflection, managing emotions, and identity development. However, the risk of unhealthy social comparisons and online harassment also exists. Individual strategies and collective efforts of social media platforms are needed to promote healthy and responsible use. Various social media features such as blogging, creating creative content, joining online groups, attending webinars, and using private messaging features, can be used to implement intrapersonal communication. Tips include setting clear goals, choosing the right platform, and being authentic. Thus, a better understanding of the impact and application of intrapersonal communication via social media is important in the ever-evolving digital era.